2017
DOI: 10.1037/hea0000410
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed visual attention drives health goal priming: An eye-tracking experiment.

Abstract: Objective: Several lab and field experiments have shown that goal priming interventions can be highly effective in promoting healthy food choices. Less is known, however, about the mechanisms by which goal priming affects food choice. This experiment tested the hypothesis that goal priming affects food choices through changes in visual attention.Specifically, it was hypothesized that priming with the dieting goal steers attention towards goal-relevant, low energy food products, which in turn increases the like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 55 publications
3
60
1
Order By: Relevance
“…They found that attention (measured with a visual probe task) towards high-calorie foods was attenuated only in participants who scored high in the level of eating restraint [37]. Similar research has shown that a health prime resulted in longer fixation time on low energy foods, also increased low-calorie food choices, and decreased high-calorie food choices [34].…”
Section: Attentionmentioning
confidence: 82%
See 1 more Smart Citation
“…They found that attention (measured with a visual probe task) towards high-calorie foods was attenuated only in participants who scored high in the level of eating restraint [37]. Similar research has shown that a health prime resulted in longer fixation time on low energy foods, also increased low-calorie food choices, and decreased high-calorie food choices [34].…”
Section: Attentionmentioning
confidence: 82%
“…It has been suggested that a determinant of choice is the attention that is assigned to certain attributes of food [7,33], and that attention can be manipulated through priming [34] or induction of mindsets [35]. A functional magnetic resonance imaging (fMRI) study showed that non-dieters made healthier choices when the attentional focus was directed to the health aspects of food, suggesting that mental simulations (comparable to the studies in mindset induction), specifically outcome simulation, may lead to healthier decisions because an individual's attention is directed towards longer-term features.…”
Section: Attentionmentioning
confidence: 99%
“…Eye tracking can also be implemented to study the processes underlying various relevant effects in consumer science such as consumers’ preferences, judgment and decision making, or goal priming. For instance, a recent study by van der Laan et al (2017) investigated how the priming of health-related motivations impacts consumers’ food choices. In this study, participants chose between high and low energy food products in a realistic online supermarket task while their eye movements were recorded with an eye-tracker.…”
Section: Physiological and Neuroscientific Measures Used In Consumer mentioning
confidence: 99%
“…People are particularly sensitive to information and consequences related to the goal that is strongest in the situation. Therefore, the goal that "frames" the situation also affects their evaluation of alternatives and the choices they make (van der Laan, Papies, Hooge, & Smeets, 2017). For example, research that will be reviewed below suggests that people may focus primarily on environmental benefits of energy saving in some and on financial benefits in other situations, depending on whether an environmental (i.e., normative) or a financial (i.e., gain) goal is activated in the situation (Spence, Leygue, Bedwell, & O'Malley, 2014).…”
Section: Introductionmentioning
confidence: 99%